(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of perioperative care and evaluate the effectiveness of implementing the enhanced recovery after surgery (ERAS) program for surgical patients at selected primary-level hospitals in Thanh Hoa province in 2025. Method: A cross-sectional descriptive study was conducted involving 132 healthcare workers directly participating in perioperative care and 72 elective surgical patients undergoing general anesthesia and managed under the ERAS protocol at four district-level general hospitals (Thieu Hoa, Hoang Hoa, Ha Trung, and Thach Thanh) from June to November, 2025. Results: Among healthcare workers involved in surgical care, 73.6% had knowledge of ERAS, although many had never previously participated in ERAS implementation. The proportion of staff receiving ERAS training during the study reached 78.6%. After training, 93.9% believed ERAS is important for patient care and supported its implementation in their hospitals. Laparoscopic surgery accounted for 56.9% of all cases; 51.4% of the patients underwent obstetric-gynecologic procedures, most of which were laparoscopic. Compliance with ERAS protocols was 68.3% in the preoperative phase, 84% intraoperatively, and 76.1% postoperatively. Time to oral intake (mean 0.81 days), time to urinary catheter removal (0.6 days), and time to drain removal (1.27 days) were all notably short. The postoperative urinary tract infection rate was 2.8%, and no major postoperative complications were recorded. Conclusion: Successful implementation of the ERAS program in primary-level hospitals improved the capacity for surgical care and reduced postoperative complications, contributing to enhanced patient outcomes and hospital performance.